Predictors of Early-Onset Cannabis Use in Adolescence and Risks for Substance Use Disorder Symptoms in Young Adulthood - Merrin, Gabriel J. (Journal of drug issues, 2022)
Early detection of risks for substance use disorders is essential to lifelong health and well-being for some youth. Very early-onset use is proposed as an indicator of risk for substance use disorders, but risk and protective factors related to early-onset use have not been identified. The current study compared risk and protective factors that distinguish early- and late-onset cannabis users from abstainers using data collected from a large community sample. The study also examined onset-group differences in participants’ reports of substance use disorder symptoms a decade later. Heavy episodic drinking (early-onset: OR = 7.29 CI = [1.60, 33.19]) and engagement with peers involved in deviant behaviors (early-onset: OR = 2.50 CI = [1.50, 4.13]) are risk factors for early-onset cannabis use. Protective factors, including parent monitoring (early-onset: OR = 0.73 CI = [0.58, 0.93]), engagement with peers involved in positive behaviors (early-onset: OR = 0.54 CI = [0.39, 0.76]), school engagement (early-onset: OR = 0.83 CI = [0.72, 0.96]), and academic grades (early-onset: OR = 0.37 CI = [0.21, 0.65]) also predicted early versus later onset-group differences. Early age of onset may be distinctly related to risk and protective factors previously associated with risks for substance use in all adolescents.